A Comparative Study of Munāsabah and Semitic Rhetoric in Sūrah Al-Fajr - Aqdi Rofiq Asnawi; Manzilah; Selamat Bin Amir (Jurnal test, 2025)
The systematic arrangement of the Qur’an has raised pros and cons among Western academies regarding its coherence. This research examines the structure of Sūrah al-Fajr as a response to orientalist criticism, which argues that the structure of the verses is not connected. By using the theoretical framework of Munāsabah and Semitic Rhetoric, this research aims to confirm the relationship of the verses in Sūrah al-Fajr to show the accuracy of their arrangement, as well as to find the relationship between Munāsabah and Semitic Rhetoric in explaining the structure of the Sūrah. This library research uses a qualitative approach and descriptive-comparative methods in analyzing data. As a result, all the verses in Sūrah al-Fajr have been proven to be well structured and coherent based on Munāsabah and Semitic Rhetoric. Both can emphasize the structure of the Sūrah, although in different ways. Munāsabah emphasizes the linear connection of verses in a Sūrah, while Semitic Rhetoric explains the structure at each level of the text. In this way, Orientalist criticism regarding the composition of the Sūrah can be refuted.